2014
DOI: 10.1002/2013jf002806
|View full text |Cite
|
Sign up to set email alerts
|

On the equilibrium profile of river beds

Abstract: [1] Despite the wide spectrum of perturbations of flow and sediment transport experienced by rivers as a result of hydrologic variations, the paradigm of morphodynamic equilibrium has long been present in the geomorphological literature where it is traditionally associated with the semiempirical notion of formative discharge, whereby the unsteady forcing is taken as morphologically equivalent to some effective steady forcing. Here we investigate the mechanisms responsible for maintaining a quasi-equilibrium be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 50 publications
5
55
0
Order By: Relevance
“…Figure a shows the equilibrium bed profiles calculated for different values of L b with a prescribed value of r B , in the limiting case of purely fluvial conditions ( a 0 =0). The picture emerging from this figure confirms the recent findings of Bolla Pittaluga et al []: at equilibrium, alluvial channels react to narrowing or widening of the cross section by modifying the flow depth and the bed profile so as to keep the total sediment discharge constant. In particular, widening channels at equilibrium experience a progressive seaward decrease of the free surface as well as a bed aggradation associated with sediment deposition, leading to a reduction of the flow depth.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Figure a shows the equilibrium bed profiles calculated for different values of L b with a prescribed value of r B , in the limiting case of purely fluvial conditions ( a 0 =0). The picture emerging from this figure confirms the recent findings of Bolla Pittaluga et al []: at equilibrium, alluvial channels react to narrowing or widening of the cross section by modifying the flow depth and the bed profile so as to keep the total sediment discharge constant. In particular, widening channels at equilibrium experience a progressive seaward decrease of the free surface as well as a bed aggradation associated with sediment deposition, leading to a reduction of the flow depth.…”
Section: Resultssupporting
confidence: 89%
“…In nature, neither fluvial forcing nor tidal forcing is steady: they undergo fluctuations associated with random variations of the hydrologic cycle, as well as with variations of the astronomical component of the tide. As a result, equilibrium may actually be defined only in statistical terms, which is not surprising in the light of the analogue problem extensively investigated in the fluvial case [see Bolla Pittaluga et al , , and references therein]. Also, note that the present analysis adopts a one‐dimensional approach.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…We build from Snow and Slingerland (), Repetto et al (), Bolla Pittaluga et al (), Duró et al (), Blom et al (), and Ferrer‐Boix et al (), and begin our analysis with four assumptions: (1) a channel reach of at least 10–20 truew̄ in length that has a well‐defined average bed surface slope; (2) statistical steady state conditions, defined as (a) bed topography adjustment rates that tend to zero across the reach and (b) comparability between the rates of total sediment supply ( Q ss ) and sediment flux ( Q sf ) between the upstream and downstream boundaries, respectively; (3) characteristic grain sizes of the bed surface D i that are tending to a spatially uniform condition; and (4) channel banks that change position at rates much less than those of bed elevation and bed surface sediment texture.…”
Section: Theory For the Local Channel Profilementioning
confidence: 99%
“…PRE1 experimental data are supplemented in Figure with corresponding data calculated for experimental results reported by Nelson et al (), field‐based results reported by Thompson et al (), and numerical simulation results reported by de Almeida and Rodríguez () and Bolla Pittaluga et al (; see supporting information S3 for details of how Δ w ( x ) and S local were calculated for each study). Nelson et al () provide experiments guided by the physical characteristics of the middle reach of the Elwha River, WA, USA; Thompson et al () provide field data for North Saint Vrain Creek, Rocky Mountain National Park, Colorado; de Almeida and Rodríguez () provide numerical simulations of the Bear River, AK, USA; and Bolla Pittaluga et al () provide numerical simulations of the Magra River, Italy, used to test theory for the equilibrium profile of riverbeds. Plotted data for de Almeida and Rodríguez (), Bolla Pittaluga et al (), and Nelson et al () are reported as steady state or equilibrium profile conditions.…”
Section: A Mechanical Link Between Channel Width Variations and The Gmentioning
confidence: 99%